"Babur-Name" As a Source of Historical and Ethnographic Science - Kazakova Rano Mashrabaevna (International Journal on Integrated Education, 2022)
This article deals with the problems of studying the historical and creative significance of the heritage of Z.M. Babur, in particular, we are talking about the significance of "Babur-name" as a source for the development of historical and ethnographic science. The article presents information that is described and reflected in the "Babur-name", as well as provides a variety of information about the political, economic, cultural life and way of life of the peoples of Central Asia at that time.